Educomunicação e a relação com o saber - Santos, Vânia Aparecida Ribeiro dos (2015)
The present work aims to investigate the conditions in which the practices of educommunication occur in a municipal public school (Primary school from 6th to 9th grades) in the suburbs of the city of São Paulo and its interference in the students-teachers interaction, in the teaching and learning methods and in the relations with the knowledge. It can be described as analytical-descriptive qualitative research, accomplished to understand which point of view students and teachers, involved in the project Nas ondas do Rádio ( In the radio waves ), have about the conditions in which the practices of educommunication occur and how those activities contribute to the students learning inside and outside school. The work was supported by authors such as Ismar de Oliveira Soares (with the concept of educommunication), Jesus Martin Barbero (concerning the relationship between youth and school education and the media processes in the current society) and Bernard Charlot (with the study of the role of schools and teachers concerning the students reality and their path towards the knowledge). Data was collected by means of documental analysis, routine observation of the Project and interviews with 07 students, 04 teachers and other subjects involved in the Project (01 Pedagogical Coordination and 01 Teacher Computer Science Adviser), besides manifestations from 04 students parents. The data was synthesized in information charts. The results allowed us to observe that the Program In the radio waves enhanced the educational process, improving the students self-esteem and making them more receptive towards the activities of production of the knowledge itself. The results also suggest that the experience lived by the students with the educommunication reflects on the daily routine of the classroom, improving the students school performance and their apprehension of the school contents. There is still indication that the students critical consciousness and creativity can be aroused with the use of instruments of communication, once the students start reading, interpreting an producing their own media plays